2022
DOI: 10.3390/nu14030664
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus Intermittent Enteral Tube Feeding for Critically Ill Patients: A Prospective, Randomized Controlled Trial

Abstract: The appropriate strategy for enteral feeding remains a matter of debate. We hypothesized that continuous enteral feeding would result in higher rates of achieving target nutrition during the first 7 days compared with intermittent enteral feeding. We conducted an unblinded, single-center, parallel-group, randomized controlled trial involving adult patients admitted to the medical intensive care unit who required mechanical ventilation to determine the efficacy and safety of continuous enteral feeding for criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Interestingly, a number of studies have also evaluated the continuous versus the bolus feeding in adult patients with opposing results [ 27 ]. A recently published RCT in critically ill patients found that patients receiving continuous EN had higher achievement rates of the goal nutritional requirement than the intermittent group [ 28 ]. However, there are studies reporting the opposite effect, making the results inconsistent for the adult critically ill population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a number of studies have also evaluated the continuous versus the bolus feeding in adult patients with opposing results [ 27 ]. A recently published RCT in critically ill patients found that patients receiving continuous EN had higher achievement rates of the goal nutritional requirement than the intermittent group [ 28 ]. However, there are studies reporting the opposite effect, making the results inconsistent for the adult critically ill population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…46 Thus, as emphasized by the guidelines, critically ill patients should have their gastric tubes removed early on, with enteral nutrition being administered promptly. 47 In case the gastric tube is not expected to be removed in the short term, other feeding routes need to be considered, such as percutaneous endoscopic gastrostomy and intermittent oro-esophageal tube feeding. 48 The present study further highlighted the importance of external validation, because we found that the discriminative ability of models was significantly lower in the validation phase than in the development phase.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines [ 19 ] recommend the use of continuous feeding rather than intermittent boluses due to the lower incidence of side effects such as diarrhea; however, despite a strong consensus the grade of the recommendation is low, mainly because of the limited sample size and heterogeneity of the populations included, and the lack of proven benefits in other outcome measures. Indeed, the debate about the best strategy to deliver enteral feeding has grown in the last years, based on the concept that an intermittent pattern could better mimic the normal daily life feeding pattern [ 63 ], and on reports that continuous enteral feeding might improve the achievement of target nutrition requirements as compared to an intermittent pattern [ 64 ]. A recent systematic review which included 19 studies that compared the two approaches found both results in favor of a continuous pattern (such as lower gastric residuals and less need for prokinetics), and in favor of an intermittent one (i.e., better digestive tract colonization, lower constipation and less evidence of tracheal aspiration of gastric contents), and confirmed that the current level of evidence is not sufficient to provide clear indications on which approach should be preferred [ 65 ].…”
Section: Discussionmentioning
confidence: 99%